Interfacial synthesis of micro-cuboid Ni0.55Co0.45C2O4 solid solution with enhanced electrochemical performance for hybrid supercapacitors. Issue 29 (15th July 2019) - Wang, Lin; Zhang, Runa; Jiang, Yang; Tian, Hua; Tan, Yu; Zhu, Kaixin; Yu, Zhifeng; Li, Wang
Abstract : The rare crystal nucleus for the growth of Ni0.55 Co0.45 C2 O4 solid solution during a biphasic interfacial reaction contribute to the formation of the hierarchical micro-cuboid structure with excellent electrochemical performance. Abstract : Efficient charge and energy storage relies essentially on the development of innovative electrode materials with enhanced electrochemical kinetics. Herein, Ni0.55 Co0.45 C2 O4 solid solution was successfully synthesized by a liquid–liquid interfacial reaction. The observation of the morphologies of Ni0.55 Co0.45 C2 O4 depicts a peculiar micro-cuboid structure composed of nanoparticles in the size range of 13 to 23 nm, benefiting the increase in the contribution of surface-controlled reactions to charge storage processes. The results from X-ray diffraction and thermogravimetric analysis demonstrate the similarity of the crystal structure and thermal decomposition behavior between Ni0.55 Co0.45 C2 O4 and CoC2 O4, and indicate that the CoC2 O4 lattice plays a role as the fundamental framework in the solid solution instead of NiC2 O4 . The electrochemical measurements show that Ni0.55 Co0.45 C2 O4 achieves a higher specific capacity of 562 C g −1 at a current density of 1 A g −1 than its counterpart NiC2 O4 /CoC2 O4 hybrids, due to this the alternative arrangement of nickel and cobalt species in the solid solution expedites the diffusion process of active ions during the electrochemical reaction. Depending on the enhancement of the electrochemical stability in the solid solution, Ni0.55 Co0.45 C2 O4 electrodes retain 87.4% of the initial capacity after 4000 cycles. The assembled Ni0.55 Co0.45 C2 O4 //AC hybrid supercapacitor attains an energy density of 38.5 W h kg −1 at a power density of 799 W kg −1 with a long cycling life (80% of the initial capacitance after 10 000 cycles). The excellent electrochemical performance suggests that Ni0.55 Co0.45 C2 O4 is a promising candidate electrode material for supercapacitors.